The role of auditor independence in the relationship between mandatory auditor rotation and audit quality: A critical literature review. - , Samwel Ndaita Bangara; Dr. Joshua Wafula Chesoli (IJRDO - Journal of Business Management, 2020)
This paper aimed at reviewing literature on the effect of mandatory auditor rotation on audit quality by bringing out the mediating effect of auditor independence on this relationship. The review utilized published papers and articles on various accounting, auditing and finance journals. The arguments that relate to auditor rotation and tenure revolved around promoting audit quality by enhancing auditors’ independence. While long auditor tenure is aimed at gaining an understanding of the client entity operations leading to improved audit quality, short audit tenure is aimed at curbing the familiarity threat that can impair auditor’s independence by bringing the fresh eye perspective to the audit that can lead to improved audit quality. From the literature it is evident that some countries have implemented mandatory auditor rotation policy while for others audit firm/partners rotation is voluntary. The results of the audit firm/partner rotation effect on audit quality are mixed and inconclusive. As such our conclusion is that the mixed results together with the regulatory changes by most governments and regulators provide a gap for future studies on mandatory auditor rotation, auditor independence and audit quality. Specific concern on how auditor independence mediates this relationship.